Epidemiological Chronicle of the First Recovered Coronavirus Disease Patient From Panama: Evidence of Early Cluster Transmission in a High School of Panama City - Hernandez, Augusto; Muñoz, Paul; Rojas, Jose C.; Eskildsen, Gilberto A.; Sandoval, Julio; Rao, K. S.; Gittens, Rolando A.; Loaiza, Jose R. (Frontiers in Public Health, 2020)
The first patient infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Panama was reported on March 9, 2020. Here, we describe the first case of recovery from coronavirus disease 2019 (COVID-19) in the country. The patient was a 49-year-old male high school teacher, who did not show any primary symptoms of COVID-19 described by health authorities as the signs for medical attention. Nonetheless, he became severely ill over the course of 2 weeks and almost lost the battle against COVID-19. The closure of a secondary school in Panama City after the identification of the first cluster of SARS-CoV-2 activity may have prevented the spread and slowed the transmission rate of COVID-19 during the early stages of invasion. This case report highlights the need to increase awareness among healthcare professionals in Latin America to consider symptoms such as anosmia and dysgeusia as the sentinel signs of COVID-19 infection in order to prevent deaths, especially in high-risk patients.